Bucharest, a Well Endowed Yet Rather Passive Capital: A Social Sustainability Perspective - Stănculescu, Manuela Sofia; Marin, Monica (Calitatea Vieții, 2011)
This paper examines social sustainability of the metropolitan area of the capital city. It looks at the recent developments in the areas of: population, poverty and social inclusion, education and training, employment and labour market, together with health and perceived quality of life. The analysis identifies several policy fields to be addressed at the national and local levels: (i) institutionalized support for vulnerable groups, (ii) participation in early childhood education and lifelong learning, and (iii) employment policies to promote the integration of the youth on the labour market and the “active ageing”.